Pengaruh Ketidakamanan Kerja, Kepuasan Kerja, dan Komitmen Organisasional terhadap Turnover Intention - Finisia Stifie Sangian; Yupiter Gulo (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this research was to determine the effect of job insecurity, job satisfaction, and organizational commitment on employee turnover intention. PT. XYZ is the main object of this study with all of its 119 employees as the population as well as the research sample. So that the sampling as research respondents uses a saturation technique. By using multiple linear regression analysis techniques, testing three key hypotheses in this study. The research findings show that three independent variables, namely job insecurity, job satisfaction and organizational commitment have a significant and positive effect on employee turn-over intention. Thus, it is necessary for companies to consider three independent variables to maintain turnover intention within the company.